Nordic Gore? Strangers, Foreigners, and the Communities We Imagine for Ourselves - Loman, Rikard (Nordic Theatre Studies, 2022)
The idea of a Nordic community, even though it was a reality in the past and is still a quite tangible idea in the present – because all Nordic countries have striking similarities – is often obscured by the more recent idea that the nation always comes first, and for quite some time now the Nordic countries have been anxious to set themselves apart from their closest neighbour in particular. In this paper, I will examine a rare – and at that, an unusually bloody and messy – Swedish-Danish theatre collaboration, Stockholms blodbad (Stockholm Bloodbath), which was staged at Malmö City Theatre, in Skåne, the southernmost of the historical provinces of Sweden, in the fall of 2016. Stockholms blodbad seemed to revive the idea of a “pure” Nordic community beneath the final coat of national varnish, but the intent was primarily to subvert and make fun of nationalistic sentiments while re-awakening a well-known, historical event in the intertwined pasts of these nations. When Stockholms blodbad premiered in 2016, the differences between Sweden and Denmark and the sense of Skåne being a border territory had been amplified by recent events and different policies regarding what is now known as “Flyktingkrisen” (The European refugee and migrant crisis) in the spring of 2015. “Flyktingkrisen” reminded us of the fact that we now live in an increasingly globalized world. Stockholms blodbad seemed to deny it. As long as nationalism skews our thoughts and perceptions of the past and the present it is impossible to imagine a future that is habitable and hospitable to all humanity.